Myocardial bridges and competitive sports fitness between past and future - Elio, Assisi; Libener, E; Grossgasteiger, S; Marine, Ottavio; Resnyak, S (Journal of Cardiovascular Medicine and Cardiology, 2023)
The myocardial bridge is an intramural course of a coronary artery in which a more or less long section of a coronary branch, instead of running normally on the epicardial surface of the heart, deepens early in the myocardium, coming to be surrounded by a ring or sleeve of muscle fiber cells that, contracting in systole, can cause an ab-extrinsic “throttling” of the artery. The guidelines for granting eligibility for competitive sports have evolved over time: from 2009, when any case of myocardial bridging indicated exclusion of eligibility, to today, when only significant bridges, i.e. ‘long’ bridges > 1 cm and > 3 mm deep, place a restriction on competitive sports activity.